Corrosion resistance of 625 nickel superalloy exposed to isothermal and thermal cycling conditions in a chloride/carbonate salt. (1st January 2023) - Bell, Stuart; de Bruyn, Mitchell; Steinberg, Ted; Will, Geoffrey
Highlights: Corrosion of 625 superalloy was tested in Na2 CO3 /NaCl molten salt at 650 °C. The alloy was assessed under both isothermal and thermal cycling conditions. Microscopy was used to analyse cross sections for corrosion thickness and structure. A 10–20 μm thick nickel based surface oxide was produced, which protected the alloy. Small concentrations of Mo, Cr and Nb were dissolved from the alloy into the salt. Abstract: Using phase change materials as thermal energy storage media is a promising approach for use in conjunction with concentrating solar thermal power (CSP) – particularly at the higher temperatures planned for next generation CSP. However, the corrosion resistance of high temperature alloys with the molten salt media proposed in these systems is critical for system longevity. The compatibility of alloy 625 in a eutectic salt mixture consisting of 59.5 wt% Na2 CO3 /40.5 wt% NaCl is investigated under isothermal conditions at 650 °C, and for thermal cycles between 600 and 650 °C. Minimal thickness loss was detected as a protective oxide was produced on the metal surface. This dense, adherent oxide consisted of a nickel oxide outer oxide layer and a nickel–chromium inner oxide layer. No major dealloying was found with this salt/alloy combination, although relatively low concentrations of alloying elements were detected in the salt. Molybdenum, chromium and niobium were found in the salt at the highest concentrations relative to their availability in the alloy. Very little nickel was detected in the salt, corroborating the protective nature of the nickel oxide surface layer. A corrosion rate of approximately 120–170 μm/year was determined for this alloy/salt combination, which was attributed to the oxide growth on the metal surface. As this oxide is protective, this corrosion rate will be significantly lower for long term exposure, potentially within the allowable corrosion rate for a thermal energy storage system.